BIOCHEMICAL AND HISTOPATHOLOGICAL OBSERVATIONS IN THE KIDNEY OF RAT AFTER METHANOL TREATMENT - KUMAR, SUNIL; RANA, S.V.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
Methanol which is an important industrial intermediate used in manufacturing of varnishes, paints, and as alternative fuelin motor vehicle. It has slow metabolism and remains in the blood for alongtime. Methanol exerts its effect through its metabolite formaldehyde and cause blood acidosis. Kidney function test along with histopathological and ultrastructural changes in the kidney after methanol exposure show that methanol cause increase in blood urea and decrease in urine specific gravity, pH, creatinine, hippuric acid, blood pH and serum albumin. Increased vascular permeability and damage to basement membrane lead to changes in glomerular structure and function. Methanol cause lipid peroxidation enlargement of glomerulus and ultrastructural changes in kidney.